2022
DOI: 10.1088/1755-1315/990/1/012023
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of electrical energy losses in a DC traction rail network during heavy traffic

Abstract: The growth of traction current leads to losses of electrical energy in the traction rail network, which entails losses for railway companies, including the Russian Railways holding. Additional losses arise due to the deterioration of the resistance of the elements, which occurs in a shorter time in terms of sections on which the movement of trains of increased mass and length is not carried out. Equations for estimation of the power and electrical energy losses in the DC traction rail network have been obtaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…The analysis of the dynamics of energy losses in electrical networks of Russia as a whole and in electrical networks of Russian enterprises and the comparative analysis of energy losses in the networks of industrialized countries showed that there are a large number of reserves to reduce energy losses and improve the energy efficiency of the Russian electrical networks [7]. According to the final report of Rosseti Siberia for 2020, the volume of electricity supply to consumers and related territorial network companies within the boundaries of balance sheet and operational responsibility amounted to 54,273.78 million kWh, which decreased by 1,515.05 million kWh or 2.72% compared with the one in 2019 (55,788.83 million kWh) [18]. The decrease in the volume of electricity supply in 2020 was due to the weather factor and the use of own energy generating facilities by some consumers [3;19;25].…”
Section: Methodsmentioning
confidence: 99%
“…The analysis of the dynamics of energy losses in electrical networks of Russia as a whole and in electrical networks of Russian enterprises and the comparative analysis of energy losses in the networks of industrialized countries showed that there are a large number of reserves to reduce energy losses and improve the energy efficiency of the Russian electrical networks [7]. According to the final report of Rosseti Siberia for 2020, the volume of electricity supply to consumers and related territorial network companies within the boundaries of balance sheet and operational responsibility amounted to 54,273.78 million kWh, which decreased by 1,515.05 million kWh or 2.72% compared with the one in 2019 (55,788.83 million kWh) [18]. The decrease in the volume of electricity supply in 2020 was due to the weather factor and the use of own energy generating facilities by some consumers [3;19;25].…”
Section: Methodsmentioning
confidence: 99%